1148 Harnessing a student network to support validation of the patient reported experience measure for over 65s attending the ED (PREM-ED 65+): Initial findings from a novel collaborative project. Issue 3 (21st February 2022) - Graham, Blair; Smith, Jason; Nelmes, Pam; Latour, Jos
Abstract : Aims/Objectives/Background: PREM-ED 65+ is an 83-item patient experience questionnaire for over-65s attending the ED. The final development stage will confirm psychometric properties in the real-world. Following recent successes of trainee-led collaborative studies, intercalated Urgent/Emergency Care students (University of Plymouth) were invited to participate in this study as student site investigators (SSIs). We aim to outline this collaborative project and report challenges and successes encountered so far. Methods/Design: A cross-sectional study was designed to administer PREM-ED 65+ to eligible patients upon discharge. Students were invited to review the protocol/SSI role at outset. Senior faculty agreed to their participation; timetable conflicts were avoided. NHS and University ethics were obtained. Thirty- two students within 19 EDs volunteered to become SSIs (64% of the cohort). All underwent training. Existing mentors were co-recruited as site PIs. Commencement—planned January 2021—was delayed until Mid-May due to administrative reasons. Results: Data collection is ongoing. Currently, twenty-two SSIs across 16 sites have recruited 272 participants in five weeks (median= 16 patients/site(R3—45); 10 accruals/SSI(R2—20)). Completion of all 83-items is near- perfect (97.8%). Sixty-four (23.5%) participants consented to a retest survey. Average respondent age is 77 years (R65—100) with more females (58.6%). No differences in arrival mode or complaint type has been observed. Participant LOS is commonly >4 hours (51.3%) with very few treated within an hour (3.3%). Per-item analysis will commence once the minimum sample (300) is achieved. Redundant items will be excluded; structural and criterion validity, and test- retest reliability will be assessed for remaining items. Student feedback will be sought to evaluate the SSI role. Conclusions: The student network has made an essential contribution. The efficiency of the collaborative model has mitigated significant commencement delay. Concerns such as conflicts with the academic programme have been allayed through involving students and faculty in design, and proactively arranging supervision and communication.